2013
DOI: 10.1111/vco.12016
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of concurrent imaging modalities for staging of dogs with appendicular primary bone tumours

Abstract: This study assessed the use of whole body computed tomography (CT) for the evaluation of metastasis in dogs with primary appendicular bone tumours compared to long bone survey radiography, bone scintigraphy and thoracic radiographs. Fifteen dogs were included in this pilot study. A construct reference standard was used for detection of bone metastasis, and negative thoracic radiographs were compared against CT. Definitive lesions were only identified on bone scintigraphy. Not all lesions agreed with the constr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
54
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(56 citation statements)
references
References 28 publications
0
54
2
Order By: Relevance
“…Three‐view thoracic radiography was the only diagnostic test to evaluate for metastatic disease in 110 (73.8%) of the cases in this study. Thoracic CT and nuclear scintigraphy are more sensitive for detecting metastatic disease, but their use can be limited by institutional availability and cost . Therefore, the potential for undocumented metastatic disease at the time of amputation in at least 1 case cannot be excluded.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Three‐view thoracic radiography was the only diagnostic test to evaluate for metastatic disease in 110 (73.8%) of the cases in this study. Thoracic CT and nuclear scintigraphy are more sensitive for detecting metastatic disease, but their use can be limited by institutional availability and cost . Therefore, the potential for undocumented metastatic disease at the time of amputation in at least 1 case cannot be excluded.…”
Section: Discussionmentioning
confidence: 99%
“…Thoracic CT and nuclear scintigraphy are more sensitive for detecting metastatic disease, but their use can be limited by institutional availability and cost. [31][32][33][34] Therefore, the potential for undocumented metastatic disease at the time of amputation in at least 1 case cannot be excluded. Chemotherapy protocols also varied by institutions.…”
Section: Discussionmentioning
confidence: 99%
“…Computed tomography is a more sensitive method for detection of pulmonary nodules than thoracic radiography . In one study, only 10% of pulmonary nodules detected on CT could be identified on thoracic radiographs .…”
Section: Introductionmentioning
confidence: 99%
“…Based on our previous work staging osteosarcoma, bone scan and CT of the lungs is recommended. 10 We recommend local staging with CT and 3-dimensional reconstruction for surgical planning of the margins of excision, that is, to determine if complete tumor resection is possible with ischiectomy or if hemipelvectomy with limb amputation is necessary.…”
Section: Discussionmentioning
confidence: 99%